ESG performance in the regulatory transformation era: a systematic thematic review (2020–2024) - Kim, Jiyeon; Yang, Wooyoung (Frontiers in Sustainability, 2026)
IntroductionThe 2020-2024 period represents a regulatory transformation era in ESG research, marked by mandatory disclosure frameworks (CSRD/ESRS, SEC climate rules, ISSB standards) replacing voluntary approaches. This creates a natural experiment for examining ESG-performance relationships under compulsory reporting. Despite extensive voluntary-period literature, limited research addresses how mandatory frameworks alter these relationships during regulatory transformation.MethodsWe conducted a systematic thematic review following PRISMA 2020 guidelines (INPLASY202570105). Comprehensive database searches (2020–2024) yielded 4,441 records; after screening (Cohen's κ = 0.89), 17 high-quality studies met inclusion criteria (12 primary search, 5 ESRS-specific supplementary search). Thematic analysis identified ten interconnected themes grounded in Dynamic Materiality Theory, Institutional Theory, and Stakeholder Theory, examining evidence across European, North American, and Asia-Pacific contexts.ResultsThree dominant themes emerged (≥59% prevalence): Performance Relationships, Mandatory Disclosure, and Methodological Evolution. ESG-performance relationships showed mixed findings under mandatory disclosure, with positive effects more pronounced in carbon-intensive sectors and European contexts. ESRS implementation revealed preparedness gaps: only 37% of EU companies fully ready, with large firms (68%) substantially outpacing medium enterprises (23%). Financial services, energy, and manufacturing showed higher preparedness (5872%) vs. retail, hospitality, and technology (2834%). Studies connected primarily to SDG 12 (n = 12), SDG 16 (n = 11), and SDG 13 (n = 6).DiscussionMandatory disclosure fundamentally alters ESG-performance relationships through standardization, harmonization, measurement convergence, and sector-specific adaptation. Findings extend Dynamic Materiality Theory by demonstrating how regulatory mandates shift stakeholder salience to external compliance requirements. The review provides insights for regulators coordinating global taxonomy alignment, firms preparing graduated implementation strategies, and investors adapting screening models. Limitations include early-phase timeframe, modest sample size (n = 17), European dominance, and English-only sources. Future research should examine longitudinal ESRS effects, ESRS-ISSB comparative implementation, and emerging market perspectives.Systematic review registration[doi: 10.37766/inplasy2025.7.0105], identifier [INPLASY202570105].